Non-linear but Trivial?

Calculus Level 2

Solve the ODE x y + y = ( x y ) 2 ln x xy'+y={(xy)}^{2} \ln{x} where y ( 1 ) = 1 3 y(1)=\frac{1}{3} . Calculate the value of y ( e ) y(e) to 3 decimal places.


The answer is 0.184.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Jakub Šafin
Jan 1, 2015

We can see that if z = x y z=xy , the equation becomes z = z 2 ln x z'=z^2\ln{x} , which is separable; its solution is given by 1 x y = 1 z = d z z 2 = ln x d x = x ( ln x 1 ) + C . -\frac{1}{xy}=-\frac{1}{z}=\int\frac{\mathrm{d}z}{z^2}=\int{\ln{x}\ \mathrm{d}x}=x(\ln{x}-1)+C\,.

Substituting for x = 1 x=1 , we find out that 3 = 1 + C -3=-1+C , so C = 2 C=-2 . Substituting x = e x=e , we find out that 1 e y = C = 2 -\frac{1}{ey}=C=-2 , so y = 1 2 e y=\frac{1}{2e} .

how did you find the idea z = xy? that's amazing bro, i wish i knew

M Natsir - 3 years, 3 months ago

Log in to reply

Bcoz the question has xy in brackets

KEVIN PAUL - 2 years, 5 months ago

I think it might be a Bit easier to See that y‘x+x can be written as the derivative of xy and Now u can substitute that.

Moritz A. - 9 months, 3 weeks ago
Ronak Agarwal
Dec 29, 2014

The function comes out to be :

1 x y + x ( l n ( x ) 1 ) = 2 \frac{1}{xy} + x(ln(x)-1) = 2

Solution for this problem :

Rewriting the differential equation we get :

x y y 2 + 1 y = x 2 ( l n ( x ) ) \large x\frac{{y}^{'}}{{y}^{2}} + \frac{1}{y} = {x}^{2}(ln(x))

Put 1 y = t \frac{1}{y} = t

Our differential equation becomes :

x t + t = x 2 l n ( x ) \large -x{t}^{'}+t={x}^{2}ln(x)

d t d x t x = x l n ( x ) \large \frac{dt}{dx}-\frac{t}{x}=-xln(x)

Now this a linear differential equation, hence we find our integrating factor and that comes out to be :

I . F = e 1 x d x = 1 x I.F = \large {e}^{\int { \frac { -1 }{ x } dx } }=\frac{1}{x}

Multiplying by integrating factor we get :

1 x d t d x t x 2 = l n ( x ) \large \frac { 1 }{ x } \frac { dt }{ dx } -\frac { t }{ { x }^{ 2 } } =-ln(x)

Integrating both sides we get :

t x = x ( 1 l n ( x ) ) + C \large \frac { t }{ x } =x(1-ln(x))+C

Putting back t = 1 y t=\frac{1}{y} we get :

1 x y = x ( 1 l n ( x ) ) + C \large \frac { 1 }{ xy } =x(1-ln(x))+C

Put x = 1 , y = 1 3 x=1,y=\frac{1}{3} to get C = 2 C=2

Hence our solution is :

1 x y + x ( l n ( x ) 1 ) = 2 \large \frac { 1 }{ xy } +x(ln(x)-1)=2

A much easier way is to express it as d d x ( x y ) = ( x y ) 2 ln x d ( x y ) ( x y ) 2 = ln x d x \displaystyle \frac{\text{d}}{\text{d}x} (xy) = (xy)^2 \text{ ln }x \Rightarrow \frac{\text{d } (xy)}{(xy)^2} = \text{ ln } x \text{ d}x . What follows is elementary integration and substitution just the way you did !!

Sudeep Salgia - 6 years, 5 months ago

Log in to reply

Good eye, good eye!

Steven Zheng - 6 years, 5 months ago

How did you arrive at this? y = 1 2 x + x 2 ( 1 ln x ) y=\frac{1}{2x+{x}^{2}(1- \ln{x})}

Steven Zheng - 6 years, 5 months ago

Very good. Your substitution is what is used to solve a general Bernouilli differential equation !

Steven Zheng - 6 years, 5 months ago

Same as I did! Btw are you preparing for JEE? And congrats for your selection in Chemistry olympiad! Hope to see you in stage 2!

Pranjal Jain - 6 years, 5 months ago

This is exactly how I did it. Great solution!

A Former Brilliant Member - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...